Handbook on Cerebral Venous Thrombosis 2007
DOI: 10.1159/000111258
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cerebral Vein and Sinus Thrombosis

Abstract: Cerebral venous thrombosis is a serious but potentially treatable cerebrovascular disorder that, unlike arterial cerebrovascular disorder, often affects young adults and children. Cerebral venous thrombosis is a challenging condition for the clinicians because of the wide spectrum of its clinical presentation. Although recognized for more than 100 years, its incidence has been underestimated in the past due to the lack of accurate diagnostic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 37 publications
2
35
0
2
Order By: Relevance
“…The observed frequency of CVST is slightly lower than that of peripartum and postpartum arterial stroke. 2,45,46 Recent clinical series and review studies 2,17,27,29,32,52,62 have confirmed the female predominance among patients suffering CVST, contrary to older reports postulating that males and females were equally affected. 44 The age group of patients demonstrating the highest frequency of CVST is those between 20 and 40 years of age.…”
Section: Incidence and Demographicsmentioning
confidence: 97%
See 3 more Smart Citations
“…The observed frequency of CVST is slightly lower than that of peripartum and postpartum arterial stroke. 2,45,46 Recent clinical series and review studies 2,17,27,29,32,52,62 have confirmed the female predominance among patients suffering CVST, contrary to older reports postulating that males and females were equally affected. 44 The age group of patients demonstrating the highest frequency of CVST is those between 20 and 40 years of age.…”
Section: Incidence and Demographicsmentioning
confidence: 97%
“…In adults, the incidence of CVST has been estimated to be as high as 3-4 cases per million people, while the respective incidence in children and neonates is higher and has been estimated to be as many as 7 cases per million. 2,23,62 A pediatric multicenter study in the US showed that CVST affects predominantly children < 6 months old. 69 It has been reported that female sex repCerebral venous sinus thrombosis: review of the demographics, pathophysiology, current diagnosis, and treatment resents a predisposing factor for developing CVST.…”
Section: Incidence and Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebral venous thrombosis (CVT) is a rare disorder with highly variable presentation that can complicate the recognition of this potentially fatal state [1][2][3]. Neuroimaging serves a critical role in the diagnosis of CVT and computed tomography (CT) is often the first imaging modality ordered; however, CT imaging of the head is not the most sensitive imaging technique, and in patients with hypercoagulable disorders, the threshold to order additional imaging studies should remain low when CVT is high on the differential diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%